A Lower Gastrointestinal Bleeding Due to a Post-Traumatic Splenosis: "Wait and See" Represents a Feasible Attitude: A Case Report. Issue 17 (April 2016) - Famà, Fausto; Giacobbe, Giuseppa; Cintolo, Marcello; Gioffré-Florio, Maria; Pallio, Socrate; Consolo, Pierluigi
Abstract : Abstract: Splenosis represents a benign condition due to an ectopic localization of splenic tissue caused by pathologic or traumatic spleen rupture. Generally, it is asymptomatic and incidentally diagnosed during imaging performed for other reasons. Occult gastrointestinal bleeding due to an extraperitoneal localization is a rare occurrence. Differential diagnosis may be very hard and includes benign and malignant neoplasms. We describe the case of a 68-year-old Caucasian man that was admitted for an increasing lower gastrointestinal bleeding associated to a vague abdominal pain. He was assessed by means of laboratory tests, as well as by endoscopic and radiological examinations, and successfully treated with an exclusive medical approach. The patient was discharged on the ninth day and currently he is doing well. This case shows that wait and see could prove a feasible attitude for the management of clinically stable patients.